(untitled) (Medicine Today, 2026)
Introduction: Hemoglobinopathies, including beta-thalassemia and Hb E, are major genetic disorders in Bangladesh. Their impact on public health is influenced by regional genetic variations, particularly in Rajshahi Division. Objective: To evaluate the influence of regional genetic variations on the prevalence of Hb E and beta-thalassemia, and their public health implications in Bangladesh, focusing on genetic traits and disease outcomes. Materials and Methods: This cross-sectional study was conducted at the Department of Haematology, Rajshahi Medical College, from January 2024 to December 2024. A total of 348 patients with suspected hemoglobinopathies were included, referred by physicians from different departments for Hb electrophoresis. Patients aged 9 months to 67 years (148 male, 190 female) were analyzed. Variables like age, sex, and different hemoglobinopathies were studied. Statistical analysis was performed using descriptive statistics, including standard deviation (SD), and p-value calculation. Results: Of the 348 samples, 192 exhibited abnormal hemoglobin profiles, while 156 had normal results. The distribution of abnormal findings was as follows: 86 (24.7%) Hb E trait, 16 (4.6%) Hb E disease, 70 (20.1%) beta-thalassemia trait, 18 (5.2%) Hb E-beta thalassemia, and 2 (0.6%) Hb S-beta thalassemia. The mean age of the patients was 22.4 years, with a standard deviation (SD) of 12.3 years. For Hb E trait, the standard deviation was 2.1, and for beta-thalassemia trait, it was 3.3. The p-value for the correlation between Hb E prevalence and regional variations was found to be < 0.05, indicating a statistically significant relationship. Additionally, the difference in disease burden between males and females was not statistically significant (p = 0.12). The highest prevalence was observed in the southern region, where the frequency of Hb E and beta-thalassemia traits reached 30%. Conclusion: This study highlights the high prevalence and regional genetic variations influencing hemoglobinopathies in Bangladesh. Targeted genetic screening and public health interventions are essential for improving patient outcomes. Medicine Today 2026, Vol.38 (1): 110-116